Analysis of the Influence of Environmental, Social, and Governance (ESG) Disclosure on Tax Reporting Aggressiveness: : The Role of Managerial Ownership and Transfer Pricing - Evy Steelyana; Joecheline Santoso (Jurnal Akuntansi dan Pajak, 2027)
Abstract.This study investigates the impact of Environmental, Social, and Governance (ESG) disclosure, managerial ownership, and transfer pricing on tax reporting aggressiveness in Indonesian companies that have implemented Enterprise Resource Planning (ERP) systems from 2019 to 2023. Tax aggressiveness is measured using the Effective Tax Rate (ETR), with ESG scores obtained from Refinitiv, while data on managerial ownership and transfer pricing are drawn from company annual and sustainability reports. Employing a quantitative approach using secondary data from firms listed on the Indonesia Stock Exchange (IDX), the study finds that ESG disclosure has a positive but statistically insignificant effect on tax aggressiveness, suggesting limited integration of ESG principles into corporate tax strategies. Similarly, transfer pricing practices show no significant influence, possibly reflecting improved regulatory compliance or oversight. In contrast, managerial ownership significantly affects tax aggressiveness, highlighting the role of internal ownership structures in shaping corporate tax behavior. These findings suggest that governance factors, particularly ownership, play a more influential role in promoting tax transparency than ESG initiatives or transfer pricing practices. The study contributes to the accounting and corporate governance literature and offers insights for policymakers aiming to design fairer and more accountable tax regulations in the era of digitalized business systems. Keywords:Corporate Governance,Tax Reporting,Sustainability Reporting, Environmental Social Governance, Tax Policy